Singularities of nilpotent Slodowy slices and collapsing levels of W-algebras - Tomoyuki Arakawa; Jethro van Ekeren; Anne Moreau (Forum of Mathematics, Sigma)
We develop techniques to construct isomorphisms between simple affine W-algebras and affine vertex algebras at admissible levels. We then apply these techniques to obtain many new, and conjecturally all, admissible collapsing levels for affine W-algebras. In short, if a simple affine W-algebra at a given level is equal to its affine vertex subalgebra generated by the centraliser of an